MODERN ARCHITECTURE AND ENVIRONMENTAL SUSTAINABILITY. (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
in the 21st century, architecture has undergone significant changes. They are aimed at ensuring environmental sustainability, innovative technologies and harmonious coexistence of man with the natural environment. Today, architecture is not only limited to creating aesthetically attractive buildings, but also focuses on minimizing its impact on the environment. Modern technologies and innovative solutions allow architects to design energy efficient, ecological and comfortable living spaces.